Development of a visible light transmission (vlt) measurement system using an open-path optical method. - S., Nurulain; Hadi, Manap (2017)
This paper describes about a visible light transmission (VLT) measurement system using an optical method. VLT rate plays an important role in order to determine the visibility of a medium. Current instrument to measure visibility has a gigantic set up, costly and mostly fails to function at low light condition environment. This research focuses on the development of a VLT measurement system using a simple experimental set-up and at a low cost. An open path optical technique is used to measure a few series of known-VLT thin film that act as sample of different visibilities. This measurement system is able to measure the light intensity of these thin films within the visible light region (535-540 nm) and the response time is less than 1s.